Artemisia absinthium ADMETدراسة الفعالية البيولوجية للمركبات الفينولية المستخلصة منبوسطة الالتحام الجزيئي، والتنبؤ بخواص - بره, أسماء; تواتي إبراهيم, نجاح (Université of eloued جامعة الوادي, 2025)
من أجل المساهمة في البحث عن مثبطات فعالة لأهداف بروتينية مرتبطة بأمراض مثل السرطان، الزهايمر، الالتهابات البكتيرية، والأكسدة، تم في هذه الدراسة استخدام منهجيات المحاكاة الجزيئية (In Silico) لدراسة الالتحام الجزيئي لمجموعة من المركبات الفينولية المستخلصة من نبتة شجرة مريم (Artemisia absinthium) [ : naringin ، P-coumaric acid ، vanillin ، caffeic acid ، vanillic acid ، chlorogenic acid ، gallic acid ، rutin ، و quercetin [ مع تسعة بروتينات [ 3EUB ، 1JIJ ، 3QX3 ، 6F86 ، VSL3 ، 4AQD ، 4EY7 ، 1M17 ، HYY2 ، GD43 ، و M17.6 ،] باستعمال برنامج AutoDock. . تم كذلك تقييم الخصائص الدوائية والسمية للمركبات المدروسة باستخدام موقعي SwissADME و Protox ، لتحليل سلوك المركبات من حيث الامتصاص، الانتشار، الثبات الحيوي، والسمية المحتملة . كشفت نتائج الالتحام الجزيئي أن مركب Naringin سجّل أعلى طاقات ارتباط مع عدة أهداف، منها -12.8 kcal/mol مع Acetylcholinesterase ، -10.84 kcal/mol مع Apoptosis factor ، و kcal/mol10.73 - مع Xanthine oxidase ، ما يدل على فعاليته كمثبط محتمل في الأمراض العصبية والالتهابية. كما أظهر Quercetin طاقات معتبرة، أبرزها -8.77 kcal/mol مع Apoptosis factor و- 8.38 kcal/mol مع Xanthine oxidase. من جهته، برز Rutin كأحد المركبات الواعدة، حيث حقق طاقة ارتباط -9.09 kcal/mol مع tyrosyl-tRNA synthetase و- 8.20 kcal/mol مع Apoptosis factor ، كما أظهر خصائص دوائية مقبولة، مما يعزز إمكانيته في التثبيط الميكروبي وتحفيز الاستماتة . كما كشفت نتائج تقييم Vanillin و P-coumaric acid عن توازن جيد بين الفعالية الدوائية In an effort to contribute to the search for effective inhibitors targeting proteins associated with diseases such as cancer, Alzheimer’s, bacterial infections, and oxidative stress, this study employed in silico molecular simulation methodologies to investigate the molecular docking of a group of phenolic compounds extracte d from Artemisia absinthium (commonly known as "Shajarat Mariam") — namely: naringin, p-coumaric acid, vanillin, caffeic acid, vanillic acid, chlorogenic acid, gallic acid, rutin, and quercetin — with nine protein targets: 3EUB, 1JIJ, 3QX3, 6F86, VSL3, 4AQD, 4EY7, 1M17, HYY2, GD43, and M17.6, using the AutoDock software. The pharmacokinetic and toxicity profiles of the studied compounds were also evaluated using the SwissADME and Protox web platforms, in order to assess absorption, distribution, bioavailability, and potential toxicity. Docking results revealed that naringin exhibited the highest binding affinities with several targets, including -12.8 kcal/mol with acetylcholinesterase, -10.84 kcal/mol with apoptosis factor, and -10.73 kcal/mol with xanthine oxidase, indicating strong inhibitory potential against neurodegenerative and inflammatory diseases. Quercetin also showed significant affinities, notably -8.77 kcal/mol with apoptosis factor and -8.38 kcal/mol with xanthine oxidase. Rutin emerged as another promising compound, recording a binding energy of -9.09 kcal/mol with tyrosyl-tRNA synthetase and -8.20 kcal/mol with apoptosis factor, along with acceptable pharmacokinetic properties, supporting its potential in microbial inhibition and apoptosis induction. Additionally, vanillin and p-coumaric acid displayed a favorable balance between pharmacological activity and absorption behavior, with vanillin scoring -5.84 kcal/mol and p-coumaric acid -7.65 kcal/mol, alongside good ADMET profiles and the ability to cross the blood-brain barrier, making them promising candidates for treating chronic neurological disorders. Based on these findings, naringin, quercetin, rutin, vanillin, and p-coumaric acid are considered promising multi-target drug candidates. The study recommends further in vitro and in vivo biological evaluations, as well as potential chemical modifications to enhance their efficacy and pharmacological properties.
ثانية ماستر كيمياء تحليلية
Keywords: : الالتحام الجزيئي (Docking) ، Artemisia absinthium L النشاط العلاجي، AutoDock 4.2 مضادات بكتيرية المحاكاة الحاسوبية – ADMET – السمية (Toxicity; Molecular docking; Artemisia absinthium; therapeutic activity; AutoDoc; antibacterial agents; computational simulation; ADMET; toxicity.